2021
DOI: 10.1038/s41366-021-00823-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of adipose tissue macrophages by bee venom phospholipase A2 attenuates high-fat diet-induced obesity

Abstract: Background/objectives Adipose tissue macrophages (ATMs) exist in either the M1 or M2 form. The anti-inflammatory M2 ATMs accumulate in lean individuals, whereas the pro-inflammatory M1 ATMs accumulate in obese individuals. Bee venom phospholipase A2 (bvPLA2), a major component in honeybee (Apis mellifera) venom, exerts potent anti-inflammatory effects via interactions with regulatory T cells (Treg) and macrophages. This study investigated the effects of bvPLA2 on a high-fat diet (HFD)-induced obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…It has been shown that bvPLA2 protected against acetaminophen-induced acute liver injury in mice [13]. In addition, a recent study reported that bvPLA2 attenuated obesity-associated hepatotoxicity in high fat diet-induced obese mice [25]. Taken together, these results suggest that bvPLA2 may have therapeutic effects not only in acute liver injury, but also chronic liver disease.…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that bvPLA2 protected against acetaminophen-induced acute liver injury in mice [13]. In addition, a recent study reported that bvPLA2 attenuated obesity-associated hepatotoxicity in high fat diet-induced obese mice [25]. Taken together, these results suggest that bvPLA2 may have therapeutic effects not only in acute liver injury, but also chronic liver disease.…”
Section: Discussionmentioning
confidence: 77%
“…Mas aun, se aumenta la concentración circulante de leptina y se reduce la adiponectina, condición que se torna crónica, y se desenlaza un cuadro proinflamatorio de bajo grado que, a mediano o largo plazo, desencadena respuestas de resistencia a la insulina, hipertensión, diabetes tipo 2, síndrome metabólico, enfermedades cardiovasculares e, incluso, cáncer 25. La quemerina es una adipocina inflamatoria asociada con aumento en la ingesta de alimentos que también ha sido implicada en la promoción de angiogénesis, hiperplasia, hipertrofia en tejido adiposo blanco, pero no en el marrón (Jeong et al, 2021). Interesantemente, se ha encontrado que las células grasas de animales obesos producen grandes cantidades de MCP-1, sustancia que atrae macrófagos al tejido graso 26.…”
Section: Obesidad: Entorno Proinflamatoriounclassified
“…As a result, low-grade inflammation in overweight people is influenced in part by dietary factors. In a high-fat diet (HFD) induced obesity model, increased infiltration of immune cell - inflammatory macrophages (type M1) - in adipose tissues, which is linked to an increase in inflammatory cytokines [35] . After the three weeks of HFD treatment onwards, an increase in macrophage-related genes was detected, and after the sixteen weeks ahead, the increase became more pronounced, culminating in the commencement of insulin resistance 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…
Fig. 2 Impact of SARS-CoV-2 infection on obese patients 33 , 34 , 35 , 36 , 37 , 38 . [SARS-CoV-2: severe acute respiratory syndrome coronavirus 2; TNF-α: tumour necrosis factor-alpha; IL-6: interleukin-6; HDL: high-density lipoprotein; LDL: low-density lipoprotein].
…”
Section: Introductionmentioning
confidence: 99%